2020
DOI: 10.14202/vetworld.2020.695-705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cocoa powder on hypertension and antioxidant status in uninephrectomized hypertensive rats

Abstract: Background and Aim: High salt diet and uninephrectomy are associated with high blood pressure with attendant cardiovascular disease conditions such as hypertension, renal damage, myocardial infarction, and stroke. The aim of this study was to investigate the beneficial effects of consumption of cocoa and cocoa-containing products in the management of high blood pressure in uninephrectomized hypertensive rats. Materials and Methods: The effect of cocoa powder on blood pressure, markers of inflammation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Several studies using animal models have established the bioavailability and antihypertensive effects associated with the intake of cocoa polyphenols. For example, in uninephrectomized hypertensive rats fed for 4 weeks with cocoa feed alone or in combination with an 8% salt diet, the authors reported reductions in both systolic and diastolic BP when compared to uninephrectomized rats fed normal feed [13]. In young spontaneously hypertensive rats, the administration of epicatechin for a two-week period resulted in a significant reduction in systolic BP [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using animal models have established the bioavailability and antihypertensive effects associated with the intake of cocoa polyphenols. For example, in uninephrectomized hypertensive rats fed for 4 weeks with cocoa feed alone or in combination with an 8% salt diet, the authors reported reductions in both systolic and diastolic BP when compared to uninephrectomized rats fed normal feed [13]. In young spontaneously hypertensive rats, the administration of epicatechin for a two-week period resulted in a significant reduction in systolic BP [14].…”
Section: Introductionmentioning
confidence: 99%